DIRECTIONS FOR OPTIMIZING FINANCIAL MECHANISMS IN THE PROCESS OF DIVERSIFYING EXPORT ACTIVITIES (Marketing Journal, 2025)
This article is devoted to a systematic analysis of the directions for optimizing financial support mechanisms in the process of export activity diversification. Under the changing global economic environment, uncertainty in international market demand, an d increasing competition, enhancing the efficiency of export operations has become a matter of strategic importance for countries. The article examines the theoretical foundations of export diversification, the role of financial mechanisms, and № 10-SON OKTA BR, 2025 -YIL 321 methodologies for assessing their effectiveness. Special attention is given to the integrated model of financial support implemented through the interaction of government policy, financial institutions, and the private sector.
Keywords: financial mechanisms; risk management; export efficiency; investment strategies; financial stability; market portfolio expansion; innovative financial instruments; international trade policy